Characterization of admitted patients with cervicofacial inflammatory process in the Maxilo facial surgery service. - Sahily Espino Otero; Julio Romero Rodríguez (Medisur)
Fundament: Cervico-facial inflammatory processes constituyen an important health problem and not to treat them since its onset could cause associated complications that could be fatal for the health of the patient. Objective: To characterize the patients with inflammatory processes who were admitted at the Maxillo-Facial service in Cienfuegos province. Method: Descriptive study that included all the patients admitted because of cervico-inflammatory processes from January 2001 to December 2003 in Cienfuegos. The variables under study were: Age, sex, data related with the disease under study, signs and symptoms on admission, applied treatment, complications, follow up and hospital stay. Results: The odontogenous processes are the most frequent and within these those caused by caries. The widespread of the process to other regions, fever, malaise and trismus were the predominant symptoms. The main cause of admission was the inadequate treatment in the initial period of the disease.